FENOMENA LAYOFF TERHADAP MOTIVASI KERJA: TINJAUAN LITERATUR SISTEMATIS - Febrinzky, Intan Tamara (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2025)
The development of the business world always experiences growth and diversity over time, resulting in significant and unavoidable competition among companies. This development forces the global business environment, especially organizations, to continually adapt. One of the adaptations made by companies is through restructuring and rationalization initiatives that ultimately lead to layoffs. This literature review aims to synthesize the findings of empirical and theoretical research on how layoff events affect various dimensions of work motivation among permanent employees. The method used in this research is a literature review and books. The sources chosen are limited to only the last 10 years. However, if the source is important to include, it can be an exception. The results of this review emphasize the importance of communication management and a transparent and fair layoff process to mitigate its negative impact on the motivation of remaining employees, thereby maintaining productivity and the sustainability of the organization post-restructure.